Acute revascularization therapy for ischemic stroke during pregnancy and post-partum in France. (June 2023) - Béjot, Yannick; Olié, Valérie; Lailler, Grégory; Grave, Clémence; Regnault, Nolwenn; Blacher, Jacques; Duloquin, Gauthier; Gabet, Amélie
Introduction: Intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) in women with ischemic stroke (IS) during pregnancy/post-partum is challenging, and recent guidelines claimed for additional information to better argue its effectiveness and safety. This observational national study aimed to describe characteristics, rates and outcomes of pregnant/post-partum women receiving acute revascularization therapy for IS compared to their non-pregnant counterparts, and pregnant women with IS not receiving such therapy. Patients and methods: In this cross-sectional study, all women aged 15–49 years hospitalized in France for IS between 2012 and 2018 were retrieved from the French hospital discharge databases. Pregnant or post-partum (⩽6 weeks after delivery) women were identified. Data about patients' characteristics, risk factors, revascularization therapy, delivery, post-stroke survival, and recurrent vascular events during follow-up were recorded. Results: Over the study period, 382 women with pregnancy-related IS were registered. Among them, 7.3% ( n = 28) received a revascularization therapy, including nine cases during pregnancy, one the same day as delivery, and 18 during the post-partum period, compared with 8.5% ( n = 1285) in women with non-pregnancy-related IS ( n = 15, 084). Treated pregnant/post-partum women had more severe IS than not-treated pregnant/post-partum. Compared with treated not-pregnant women, they were younger, but did not differ regarding other characteristics including stroke severity. There were no differences in systemic or intracranial hemorrhages or in the length of hospital stay between pregnant/post-partum women compared with treated not-pregnant women. All women receiving revascularization during pregnancy had a live baby. After a mean follow-up of 4.3 years, all pregnant/post-partum women were alive, one had recurrent IS and none had other vascular events. Discussion and conclusion: Only a few women with pregnancy-related IS were treated with acute revascularization therapy, but this was proportionately similar to their non-pregnant counterparts, from whom they did not differed regarding characteristics, survival, and risk of recurrent events. These findings suggest that stroke physicians applied treatment strategies of IS in a similar way regardless of pregnancy in France, and this attitude was an anticipation but consistent with the recently published guidelines on the topic.